The House of Jevayla Ye - Mumbai Archive Project Team (Jio Institute, 2024)
Along with her daughter, Natasha, she runs the popular Instagram page @Jevayla_Ye (89k followers) and ‘The House of Jevayla Ye’ page on Facebook, where the mother-daughter duo shares the preparation processes of dishes from East Indian cuisine. In their own words, ‘The House of Jevayla Ye venture aims to introduce you to our humble authentic East Indian masalas. Sukhala!’ [1]